How Students Perceive the Ideal Teachers of English: A Descriptive-Reflective Study at Senior High School in Pangkep Regency - Metimukarrama Metimukarrama (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Muslim Maros, 2018)
The present study is about a study on the characteristics of the ideal English teacher as perceived by students of SMA Negeri 1 Pangkajene and SMA Negeri 2 Pangkajene in Pangkep regency. There were 20 students involved as the participants of the study which were selected purposively from those schools. The study intended to answer the main research question related to the characteristic of ideal English teacher by formulating four sub-research questions about the characteristics of ideal English teacher in the terms of: 1) pedagogical competence, 2) personal competence, 3) social competence and 4) professional competence. The research data were collected by using interview and observation technique. Then the data were analyzed by applying descriptive data analysis since this study aimed at describing how the students perceive the ideal teacher of English. The procedure of analyzing the data involved data reduction, data display, and drawing conclusion or verification. The result of the study indicated that the students mostly perceive the ideal English teacher based on the four teachers competence: pedagogical, personal, social, and professional competence. However there were additional characteristics revealed by the students which are related to the physical appearance of the teacher.